Expression, purification, crystallization and preliminary crystallographic analysis of human Rad GTPase - Yanuar, Arry (International Union of Crystallography, 2005)
Human Rad is a new member of the Ras GTPase superfamily and is overexpressed in human skeletal muscle of individuals with type II diabetes. The GTPase core domain was overexpressed in Escherichia coli and purified for crystallization. Crystals were obtained at 293 K by vapour diffusion using a crystallization robot. The crystals were found to belong to space group P2(1), with unit-cell parameters a = 52.2, b = 58.6, c = 53.4 Å, β = 97.9°, and contained two Rad molecules in the crystallographic asymmetric unit. A diffraction data set was collected to a resolution of 1.8 Å using synchrotron radiation at SPring-8.